Software-defined networking based network virtualization for mobile operators. (January 2017) - Narmanlioglu, Omer; Zeydan, Engin
Abstract: Software-defined networking (SDN) paradigm provides many features including hardware abstraction, programmable networking and centralized policy control. One of the main benefits used along with these features is core/backhaul network virtualization which ensures sharing of mobile core and backhaul networks among Mobile Operators (MOs). In this paper, we propose a virtualized SDN-based Evolved Packet System (EPS) cellular network architecture including design of network virtualization controller. After virtualization of core/backhaul network elements, eNodeBs associated with MOs become a part of resource allocation problem for Backhaul Transport Providers (BTPs). We investigate the performance of our proposed architecture where eNodeBs are assigned to the MOs using quality-of-service (QoS)-aware and QoS-unaware scheduling algorithms under the consideration of time-varying numbers and locations of user equipments (UEs) through Monte Carlo simulations. The performances are compared with traditional EPS in Long Term Evolution (LTE) architecture and the results reveal that our proposed architecture outperforms the traditional cellular network architecture.